2016
DOI: 10.3389/fneur.2016.00040
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization and Manipulation of the Cervical Spine in Patients with Cervicogenic Headache: Any Scientific Evidence?

Abstract: Cervical mobilization and manipulation are frequently used to treat patients diagnosed with cervicogenic headache (CEH); however, there is conflicting evidence on the efficacy of these manual therapy techniques. The purpose of this review is to investigate the effects of cervical mobilization and manipulation on pain intensity and headache frequency, compared to traditional physical therapy interventions in patients diagnosed with CEH. A total of 66 relevant studies were originally identified through a review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 29 publications
(48 reference statements)
1
20
1
4
Order By: Relevance
“…SMT is defined as a manually applied, high velocity and low amplitude force, directed at specific spinal segments to create joint movement at or beyond the normal joint end-range (Gross et al, 2010). A number of contemporary systematic reviews have shown that SMT might be a beneficial modality for reducing pain associated with CGHA (Chaibi & Russell, 2012;Coelho et al, 2019;Garcia, Arnold, Tetley, Voight, & Frank, 2016;Racicki, Gerwin, DiClaudio, Reinmann, & Donaldson, 2013). These systematic reviews based their conclusions on multimodal treatment studies that incorporated or combined massage, spinal mobilization and exercise, with and without SMT (Chaibi & Russell, 2012;Coelho et al, 2019;Garcia et al, 2016;Racicki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…SMT is defined as a manually applied, high velocity and low amplitude force, directed at specific spinal segments to create joint movement at or beyond the normal joint end-range (Gross et al, 2010). A number of contemporary systematic reviews have shown that SMT might be a beneficial modality for reducing pain associated with CGHA (Chaibi & Russell, 2012;Coelho et al, 2019;Garcia, Arnold, Tetley, Voight, & Frank, 2016;Racicki, Gerwin, DiClaudio, Reinmann, & Donaldson, 2013). These systematic reviews based their conclusions on multimodal treatment studies that incorporated or combined massage, spinal mobilization and exercise, with and without SMT (Chaibi & Russell, 2012;Coelho et al, 2019;Garcia et al, 2016;Racicki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Наиболее эффективными методами лечения ЦГГБ являются неле-карственные воздействия, при этом необходимо опреде-лить подгруппы пациентов для каждого отдельного вида терапии и исследовать эффективность мультимодальных вмешательств [13,14,16]. В то же время методы мануаль-ной медицины способствуют также и коррекции верте-брогенных влияний на кровоток в вертебробазилярном бассейне [3,8,10].…”
Section: головная боль связанная с ангиопластикой каро-тидных или поunclassified
“…Aus dem Bereich der symptomatischen Kopfschmerzdiagnosen sind die Myoarthropathie (Tendomyopathie der Kaumuskulatur, kraniomandibulä-re Dysfunktion) sowie der anhaltende idiopathische Gesichtsschmerz wichtige Differenzialdiagnosen. (24).…”
Section: Epidemiologie Und Differenzialdiagnosenunclassified